Effect of silver nanoparticles on hardness in medium-density fiberboard (MDF) - Taghiyari Hamid R; Norton J (iForest - Biogeosciences and Forestry, 2015)
Effect of silver nanoparticles on hardness in medium-density fiberboard (MDF) was studied here. A 400 ppm aqueous nanosilver suspension was used at three consumption levels of 100, 150, and 200 mL kg-1, based on the dry weight of wood fibers; the results were then compared with the control panels. The size range of silver nanoparticles was 30-80 nm. Composite mats were hot-pressed for 6, 8, and 10 min. Results showed that the uniform and even dispersion of nanoparticles throughout the MDF-matrix significantly contributed to an increase in the hardness at lower hot-press time of 6 min. In the longer hot-press times, however, over-heating of the mat resulted in significant a decrease of hardness values. Significant high correlation was observed between water absorption and thickness swelling.